Photodynamic Therapy: Esophagus. (2002) - Gossner, L
Abstract : Photodynamic therapy (PDT) is a minimally invasive, organ-preserving therapeutic modality, involving three separate components - light, oxygen and a photosensitizing drug. The principles of PDT are described, and the indications for its use are reviewed. Although a widespread clinical application for PDT has not yet emerged, PDT may establish itself as an endoscopic procedure with few or no side effects in the treatment of Barrett's esophagus (high-grade dysplasia and early carcinoma) and, in selected cases, for the treatment of early squamous cell carcinoma.